Corrosion fatigue failure analysis and service life prediction of high strength steel wire. (March 2020) - Xue, Songling; Shen, Ruili; Chen, Wei; Miao, Rusong
Highlights: The fatigue tests were carried out on the specimens after different degrees of corrosion. The S-N curves of different degrees of corrosion were given. The steel wire life model considering the effect of corrosion was proposed. How to design the test considering the corrosion fatigue coupling effect at the same time needs to be further studied. Abstract: In this paper, corrosion fatigue failure of high-strength steel wire was studied based on the actual cable or sling in the bridge, and the service life prediction formula considering the corrosion effect was put forward, which provides a force basis for future research. Firstly, six groups of steel wires with different corrosion degrees were analyzed by a 3D scanner, and the corrosion characteristics of different specimens were given. Secondly, S-N curves of different corrosion degrees and S-N-φ surface were given by fatigue tests of six groups of steel wires with different corrosion degrees. The results show that the S-N curve becomes steeper with the increase of steel wire corrosion. Fatigue life considering the corrosion is much lower than that without considering corrosion. Finally, a fatigue life prediction model considering the corrosion fatigue coupling effect was proposed. The calculation results show that the fatigue life prediction model considering the corrosion fatigue coupling effect can reflect the effect of the corrosion fatigue coupling effect to some extent.